2014
DOI: 10.3171/2013.9.jns13664
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal-facial nerve “side”-to-side neurorrhaphy for persistent incomplete facial palsy

Abstract: Object Hypoglossal-facial nerve neurorrhaphy is a widely used method for treating complete facial palsy. However, the classic surgical procedure using a “side”-to-end neurorrhaphy is not suitable for incomplete facial palsy (IFP), because sectioning of the facial nerve for neurorrhaphy compromises remnant axons and potential spontaneous reinnervation. For the treatment of persistent IFP, the authors investigated in rats a modified method using hypoglossal-facial nerve “side”-to-side neurorrhaphy. Methods An I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…In two cases, a follow-up EMG after 4 weeks showed nerve conduction. This phenomenon was described previously by other authors who described the ingrowth of nerve fibers in the end-to-side [2,[4][5][6][7][8][9] or the side-toside anastomosis [3,10]. In the aforementioned studies, a nerve sheath was cut at the site before the anastomosis was made to ensure direct contact of nerve fibers between the end and the side of the fused nerves.…”
Section: Discussionmentioning
confidence: 57%
“…In two cases, a follow-up EMG after 4 weeks showed nerve conduction. This phenomenon was described previously by other authors who described the ingrowth of nerve fibers in the end-to-side [2,[4][5][6][7][8][9] or the side-toside anastomosis [3,10]. In the aforementioned studies, a nerve sheath was cut at the site before the anastomosis was made to ensure direct contact of nerve fibers between the end and the side of the fused nerves.…”
Section: Discussionmentioning
confidence: 57%
“…However, a prerequisite for this technique is the appropriate anatomical structure that allows the approximation of two parallel nerve trunks. For cases not allowing this, various other techniques have been developed to connect parallel nerves to the side-to-side bridge technique with nerve grafts [14, 20, 36] or synthetic conduits [26]. The obvious weaknesses of the present study are the differences in the regeneration capacity as well as the differences of the nerves between rodents and humans.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of persistent incomplete facial paralysis, we have recently demonstrated that rapid reinnervation of the whisker pad can be achieved by the HN–FN ‘side’-to-side neurorrhaphy using an interpositional nerve autograft with preservation of the injured FN 8. Thus, this method may be rapidly performed on patients without compromising the spontaneous reinnervation by the remaining FN axons.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, we used predegenerated nerve grafts (PNG) in our experiments to provide a supportive environment for axonal regeneration. The nerve graft was prepared by sectioning the peroneal nerve and using its distal segment 1 week later 8 9. This procedure is based on the concept that Schwann cells transdifferentiate into repair cells distal to the nerve injury site, thus providing a permissive environment for axon regrowth 10–12.…”
Section: Introductionmentioning
confidence: 99%